Islamic banks as a main driver of Islamic financial industry activity: Al-Rajhi Saudi Bank model - benhamida, asma; hassiba, semira (Finance and Business Economies Review, 2023)
This research paper aims to show the role of Islamic banks in revitalizing the Islamic financial industry with reference to the experience of the Al-Rajhi Saudi Bank, which is considered a successful experience in this field, especially since Saudi Arabia occupies the leadership in the field of Islamic finance in recent times, in addition to extracting the need of Islamic financial institutions To the work of Islamic banks as the main pillar of this industry, by providing a variety of financial products with the aim of supporting the work of these institutions, as Islamic banks seek to mobilize the financial resources deposited with them to activate long-term investment, and to get rid of excess liquidity, if it exists; In addition to managing risks if they occur. this research paper has reached to That Islamic banks due to the advantages they have, are able to strengthen the relationship between the various institutions of the Islamic financial industry within the framework of functional integration among them, which allows to expand the activity of this industry and increase its competitiveness with its traditional counterpart